Kraft Pulping of Sikkim Woods - Guha, S. R. D.; Sharma, Y. K.; Jain, D. K.; Kumar, Krishna; Karira, B. G. (Indian Forester, 1976)
The paper reports the results on sulphate pulping of four soft woods (viz., Larix griffithii, Abies spectabilis, Tsuga durnosa, Picea spinulosa) and two hardwoods (viz., Acer spp., Betula spp,) of Sikkim origin, as well as proximate analysis and fibre dimensions. The lignin content of the softwoods is higher than that of the hardwoods whereas holocelulose is lower as usual. When pulped individually under, identical conditions East Himalayan fir gave the best results amongst softwoods and Birch was found better in the case of hardwoods. Furnish obtained by blending the pulps of individual species and those obtained by cooking the mixture of all the species gave almost similar strength properties. The results have revealed that all these woods are suitable for manufacture of high strength kraft papers.